2020
DOI: 10.1371/journal.pone.0234310
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of influencing factors of no/low response to preoperative concurrent chemoradiotherapy in locally advanced rectal cancer

Abstract: The aim of this study is to investigate the influencing factors associated with no/low response to preoperative concurrent chemoradiotherapy (CCRT) for locally advanced rectal cancer (LARC) patients. A total of 79 patients were included in this prospective study. Fifteen factors that might affect the resistance to CCRT were included in this logistic regression analysis, these factors include the general clinical data of patients, the expression status of tumor stem cell marker CD44v6 and the volumetric imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
1
0
0
Order By: Relevance
“…Previous studies have shown that both c-Myc (65, 66) and CD44 (67-71) have the characteristics of tumor stem cell marker factors, so we believe that the two genes are eligible for irradiation resistance markers. In fact, the positive correlation between the expression level of these two genes and tumor irradiation resistance has also been confirmed in several studies (72)(73)(74)(75)(76)(77). Therefore, we speculated that the regulation of miRNA-96-5p on irradiation resistance of rectal cancer cells was not only related to the abnormal activation of Wnt signal transduction pathway, but also may be related to the "stem" characteristics of tumor cells.…”
Section: Discussionsupporting
confidence: 56%
“…Previous studies have shown that both c-Myc (65, 66) and CD44 (67-71) have the characteristics of tumor stem cell marker factors, so we believe that the two genes are eligible for irradiation resistance markers. In fact, the positive correlation between the expression level of these two genes and tumor irradiation resistance has also been confirmed in several studies (72)(73)(74)(75)(76)(77). Therefore, we speculated that the regulation of miRNA-96-5p on irradiation resistance of rectal cancer cells was not only related to the abnormal activation of Wnt signal transduction pathway, but also may be related to the "stem" characteristics of tumor cells.…”
Section: Discussionsupporting
confidence: 56%